Whole-exome sequencing reveals known and novel variants in a cohort of intracranial vertebral–basilar artery dissection (IVAD). Issue 11 (November 2018) - Wang, Kun; Zhao, Sen; Zhang, Qianqian; Yuan, Jian; Liu, Jiaqi; Ding, Xinghuan; Song, Xiaofei; Lin, Jiachen; Du, Renqian; Zhou, Yangzhong; Sugimoto, Michihiko; Chen, Weisheng; et al.
Abstract Intracranial vertebral–basilar artery dissection (IVAD) is an arterial disorder leading to life-threatening consequences. Genetic factors are known to be causative to certain syndromic forms of IVAD. However, systematic study of the molecular basis of sporadic and isolated IVAD is lacking. To identify genetic variants contributing to the etiology of IVAD, we enrolled a cohort of 44 unrelated cases with a clinical diagnosis of isolated IVAD and performed whole-exome sequencing (WES) for all the participants; a trio exome sequencing approach was used when samples from both parents were available. Four previously reported disease-causing heterozygous variants (three inCOL3A1 and one inFBN1 ) and seven novel heterozygous variants in IVAD-related genes were identified. In addition, six variants in novel IVAD genes including twode novo heterozygous nonsynonymous variants (each inVPS52 andCDK18 ), two stop-gain variants (each inMYH9 andLYL1 ), and two heterozygous biallelic variants inTNXB were considered to be possibly contributing to the phenotype, with unknown significance according to the existing knowledge. A significantly higher mutational rate of IVAD candidate genes was observed in patients versus our in-house controls (P  = 0.002) (DISCO study, http://www.discostudy.org/, n  = 2248). Our study provided a mutational landscape for patients with isolated IVAD.